COMPARATIVE ANALYSIS BETWEEN NURSING CORE COMPETENCY STANDARDS OF AUSTRALIA AND THE PHILIPPINES - Rainier C. Moreno-Lacalle (Belitung Raya Foundation, Indonesia, 2019)
Philippines as one of the top producers of nurses worldwide must benchmark its national nursing standards to the rest of the world. Therefore, the standards must be compared and contrasted with other countries like Australia. The main purpose of this study is to compare and contrast nurse’s competency and performance indicators between the Philippines and Australia nursing competency system. This is a review article guided by Donnelly and Weichula’s Qualitative- Comparative Analysis (QCA). The process includes identification of the condition of interest, dichotomization and development of truth tables. Two official documents namely the Philippines’ National Nursing Core Competency Standards and Australia’s National Competency Standards for the Registered Nurse were selected as the condition of interest. Findings show that Australia adopted a one pronged-generalist, non-linear approach, and policy-based nursing education system while the Philippines emphasized on three-pronged specialization, work-based, and linear approach nursing competency standards. The Australia and Philippine nursing competency trails a different path in adopting standards for nursing education system. The strengths and weaknesses of each national nursing competency standards were discussed.